The effects of personas on creative codesign of work equipment: an exploratory study in a real setting. Issue 4 (1st October 2016) - Bornet, Corinne; Brangier, Eric
Abstract: Research on personas often lacks real assessment of their pros and cons. This paper proposes a measure of the effects of personas on the creativity of a team involved in the improvement of working conditions. It describes an exploratory study carried out in a real setting, which explores the effects of two sources of information on collective creativity. Two design teams were informed about the changes induced on operators and driver deliverymen following the introduction of new equipment. One team had a written list of findings and the other team a set of personas, also in written format. Each team conducted a design session to generate and select ideas. In a second phase, a steering committee was responsible for validating the ideas to be implemented. These sessions were videotaped, transcribed and analysed. The results show that the team with personas generated the most appropriate ideas and had the highest argumentative activity, which was used to filter the largest number of ideas. These results therefore highlight the positive influence of personas on the quality of ideas and the exchange of points of view within a design team. They do not, however, enable us to determine whether personas introduce an empathic process.